Effects of probiotics-encapsulated live feed on growth and survival of juvenile Clarias batrachus (Linnaeus, 1758) after differential exposure to pathogenic bacteria (SAARC Journal of Agriculture, 2018)
Growth and survival of Clarias batrachus juveniles (10-day old) fed probiotic Bacillus cereus (KR809412) encapsulated live feed (chironomid larvae) have been evaluated after differential exposure to the pathogenic Aeromonas hydrophila (MTCC 1739). Catfish juveniles were stocked at a density of 30 fish per tank in five experimental groups (T1-T5) along with a control group in triplicate and fed twice @ 5% of body weight day-1 for four weeks. Groups T1 and T2 were fed probiotic-encapsulated (PR) or pathogen-inoculated (PGN) live feed respectively, for initial three weeks. During this period groups T3 (PGN-PR-PR), T4 (PR-PGN-PR), and T5 (PR-PR-PGN) were differentially exposed to the pathogen. Live feed without probiotic and pathogen was offered to the control group throughout the experimental period and all other treatment groups (T1-T5) during the 4th week. Continuous exposure to probiotics in group T1 resulted in significantly higher (P